Physiotherapy interventions in treating patients following total hip arthroplasty:a narrative review - Ahmed, Faruq; Islam, Shofiqul; Hassan, Nazmul; Ahmed, Shahoriar; Sultan Nahid, Zahid Bin; Hoque Rase, Aminul (2024)
Introduction. Total hip arthroplasty (THA) is the most common, successful modern surgical intervention in orthopedic practice.Physiotherapy interventions are a major part of patient rehabilitation following THA. This study aimed to evaluate the effectivenessof physiotherapy interventions for improving functional outcomes following THA.Methods. This narrative review was conducted on electronic platforms and databases, including PubMed, PEDro, CINAHL,and EMBASE, using a combination of search terms related to “physical therapy”, “physiotherapy”, “physical exercise”, “physiotherapy intervention”, “hip arthroplasty”, “total hip arthroplasty”, and “hip joint replacement”. Inclusion criteria included randomized controlled trials or clinical trials published in English from 2014 to 2021. Where THA was recognized as the primaryconcern, and physiotherapy management was one of the treatment options.Results. The initial search of the databases revealed a total of 77 studies. Of those studies, 19 were selected as potentiallymeeting the inclusion criteria. Eventually, 10 studies were analyzed for the narrative review’s final conclusions. The evaluationssupported the hypothesis that physiotherapy interventions have favorable outcomes for patients with THA.Conclusions. After reviewing, it has been revealed that physiotherapy can improve physical function, balance, range of motion,muscle strength, and gait pattern following THA.
Keywords: physiotherapy; physical therapy; total hip arthroplasty; hip joint replacement